The genetics of congenital heart disease: The role of advanced genomic approaches - Saacks, Nicole; Spracklen, Timothy; Eales, James; Shaboodien, Gasnat; Keavney, Bernard; Zühlke, Liesl (SA Heart Journal, 2021)
As the leading non-infectious cause of paediatric morbidity and mortality worldwide, congenital heart disease (CHD) is a significant social and healthcare burden, especially in low- and lower-middle-income countries, including South Africa. The aetiology of CHD is poorly understood, though heritable genetic factors have been shown to contribute to the risk of CHD in individuals of European ancestry. In this review, we highlight the impact that advanced genomic approaches have had on the understanding of the role of genetics in CHD. We also summarise current knowledge of the genetics of CHD in Africa, and the challenges and opportunities for conducting genomic research in these populations. Chromosomal microarrays and next-generation sequencing platforms allow for high-throughput screening of patients for genetic mutations and show great potential for the identification of genetic causes of CHD. Advancing our understanding of the genetic architecture and risk factors associated with CHD in patients of African descent is the fi rst step towards improving CHD diagnosis and management. Therefore, exploring the genetics of CHD has the potential to improve the quality of life for children born with CHD in Africa, by enabling clinicians to identify familial inheritance patterns and predict recurrent risks and prognostic outcomes pre- and post-surgical intervention.